Current understanding of cortical structure and function in migraine. (November 2019) - Tolner, Else A; Chen, Shih-Pin; Eikermann-Haerter, Katharina
Objective: To review and discuss the literature on the role of cortical structure and function in migraine. Discussion: Structural and functional findings suggest that changes in cortical morphology and function contribute to migraine susceptibility by modulating dynamic interactions across cortical and subcortical networks. The involvement of the cortex in migraine is well established for the aura phase with the underlying phenomenon of cortical spreading depolarization, while increasing evidence suggests an important role for the cortex in perception of head pain and associated sensations. As part of trigeminovascular pain and sensory processing networks, cortical dysfunction is likely to also affect initiation of attacks. Conclusion: Morphological and functional changes identified across cortical regions are likely to contribute to initiation, cyclic recurrence and chronification of migraine. Future studies are needed to address underlying mechanisms, including interactions between cortical and subcortical regions and effects of internal (e.g. genetics, gender) and external (e.g. sensory inputs, stress) modifying factors, as well as possible clinical and therapeutic implications.